Molecular dynamics simulations and Gaussian network model for designing antibody mimicking protein towards dengue envelope protein - Chong, Wei Lim; Vao-soongnern, Visit; Nimmanpipug, Piyarat; Tayapiwatana, Chatchai; Lin, Jung-Hsin; Lin, Yi-Ling; Chee, Hui Yee; Md Zain, Sharifuddin; Abd Rahman, Noorsaadah; Lee, Vannajan Sanghiran (Elsevier BV, 2022)
The number of people infected with dengue, as reported by WHO, reaches 390 million yearly, and the global incidence of dengue has grown tremendously. Specific drugs for treating dengue are under development while several antibodies bound to domain III (DIII) envelope (E) protein of dengue virus (DENV) were found to prevent the viral entry process. In this study, designed ankyrin repeat proteins (DARPins), one of the versatile scaffolds for protein–protein interactions were explored for their potential in mimicking the interactions of antibodies to bind with domain III (DIII) E protein of DENV-2. DARPin and DIII complexes were first generated through molecular docking process and underwent molecular dynamics simulations on AMBER14 programme for 100 ns. Free energy calculations were performed under Molecular Mechanics Generalized Born Surface Area (MM-GBSA) to predict the binding affinity of the proteins and also locate the important residues on the binding interface. DARPin template with higher potential for DIII DENV-2 was then further designed through computational site-directed mutagenesis to improve its binding affinity for DIII DENV-2. Gaussian Network Model (GNM), an elastic network model, was then used to investigate the global mode shape or, in other words, dynamics of the proteins. Minima of global mode shape were residues with restricted motion, and some of them were important residues involved in binding interactions. Global mode shape and binding free energy were observed to be correlated as protein complex with low binding free energy has a lower mode shape, or lower mobility. The simulated techniques provide valuable tools in understanding the structural dynamics and energy contribution in designing the DARPins in their binding to the E protein of DENV-2.